The Role of Augmented Reality in Interactive Mobile Learning: Current Trends and Future Directions - Ardiansyah, T (Journal Mobile Technologies (JMS), 2024)
The rapid growth of digital technology has redefined education by transforming how knowledge is accessed, constructed, and experienced. This study investigates the role of augmented reality (AR) in mobile learning as a catalyst for interactive, experiential, and learner-centered education. Using a qualitative descriptive approach, it synthesizes findings from recent peer-reviewed studies published between 2021 and 2024 to identify trends, challenges, and pedagogical implications of AR integration in mobile environments. The results reveal four dominant dimensions shaping current AR-based learning: technological development, pedagogical adaptation, learner engagement, and institutional readiness. AR enhances motivation, spatial reasoning, and conceptual understanding by merging real-world contexts with virtual content. However, the study also highlights persistent barriers, including uneven infrastructure, insufficient teacher preparation, and the absence of cohesive instructional frameworks. Meaningful AR adoption requires alignment between technology, pedagogy, and learner psychology—an equilibrium consistent with the Technological Pedagogical Content Knowledge (TPACK) model. The research concludes that AR’s transformative potential lies not in its novelty but in its capacity to foster inquiry, reflection, and collaboration. Future work should emphasize longitudinal studies, cross-disciplinary collaboration, and equitable policy development to ensure that AR evolves into a sustainable and inclusive component of digital education.